Gente alguem me ajuda a fazer essa equação x (x+9) + (x+9) = 0
Soluções para a tarefa
Respondido por
0
x (x+9)(x+9) = 0
Para a equação ser igual a zero, temos:
x=0 ou x+9=0 ⇒ x=-9
Para a equação ser igual a zero, temos:
x=0 ou x+9=0 ⇒ x=-9
Respondido por
0
Ola Maarii
x * (x + 9) + (x + 9) = 0
(x + 1)*(x + 9) = 0
x1 = -1
x2 = -9
.
x * (x + 9) + (x + 9) = 0
(x + 1)*(x + 9) = 0
x1 = -1
x2 = -9
.
Perguntas interessantes
Ed. Física,
1 ano atrás
Inglês,
1 ano atrás
Geografia,
1 ano atrás
Administração,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás